2020
DOI: 10.1074/jbc.ra119.012047
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-15b contributes to depression-like behavior in mice by affecting synaptic protein levels and function in the nucleus accumbens

Abstract: Major depression is a prevalent affective disorder characterized by recurrent low mood. It presumably results from stress-induced deteriorations of molecular networks and synaptic functions in brain reward circuits of genetically-susceptible individuals through epigenetic processes. Epigenetic regulator microRNA-15b inhibits neuronal progenitor proliferation and is up-regulated in the medial prefrontal cortex of mice that demonstrate depression-like behavior, indicating the contribution of microRNA-15 to major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…The miR-335 participates in treating severe depression by targeting glutamate metabotropic receptor 4 (GRM4) [ 54 ]. miR-15b is upregulated in the medial prefrontal cortex of depression like mice [ 55 ]. miR-101 is decreased in the ventrolateral orbital cortex (VLOs) of chronic unpredictable mild stress (CUMS) rat brain and targets dual-specific phosphatase 1 (DUSP1) to modulate depressive-like behaviors [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-335 participates in treating severe depression by targeting glutamate metabotropic receptor 4 (GRM4) [ 54 ]. miR-15b is upregulated in the medial prefrontal cortex of depression like mice [ 55 ]. miR-101 is decreased in the ventrolateral orbital cortex (VLOs) of chronic unpredictable mild stress (CUMS) rat brain and targets dual-specific phosphatase 1 (DUSP1) to modulate depressive-like behaviors [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using chronic unpredictable mild stress in male animals, Fang et al found small increases in miR-451-5p expression in rat serum exosomes [ 48 ]; we also found a small increase in miR-451-5p in the hippocampus in males, yet we found further increase in female MS animals. Another study using the mouse chronic unpredictable mild stress model found that increased miR-15b-5p induced depression-like behavior and reduced the numbers of neuron boutons from medial PFC [ 56 ]. In MS animals, we found increases in miR-15b-3p in the PFC, which could suggest neuronal morphology changes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, miR-15b has been shown to inhibit angiogenesis in proliferative diabetic retinopathy via targeting VEGFA, inhibit vascular smooth muscle cells in peripheral artery disease via targeting IGF1R, counteract senescence-associated mitochondrial dysfunction in skin aging via targeting SIRT4, and suppress Th17 Differentiation in multiple sclerosis by targeting O-GlcNAc [ 42 , 43 , 44 , 45 ]. In contrast, miR-15b has been found to augment cell apoptosis in Parkinson’s disease via targeting the GSK-3β/β-catenin signaling pathway, contribute to depression-like behavior in mice by affecting synaptic protein levels and function in the nucleus accumbens, deteriorate cardiomyocyte apoptosis in myocardial infarction via targeting Bcl-2/MAPK3, and contribute to extra-cellular matrix degradation in intervertebral disc degeneration via targeting SMAD3 [ 46 , 47 , 48 , 49 ]. In accordance with our findings, miR-92b-3p can suppress angiotensin II-induced cardiomyocyte hypertrophy via targeting HAND2, protect astrocyte neurons against oxygen and glucose deprivation, promote spinal cord neurite growth and functional recovery through the PTEN/AKT pathway [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%